Perencanaan Ulang Struktur Gedung Rumah Susun Negara Kementerian Keuangan 25 Lantai Tahan Gempa Menggunakan Sistem Ganda (Dual System) di Jakarta Barat - Rizci Purna Dewanti; Dedy Rutama; Agastyasa Ghea Amarta (Universitas Batanghari Jambi, 2026)
Urban population growth has driven a high demand for vertical housing that is efficient and highly resilient to lateral loads. The Ministry of Finance's State Apartment Building in West Jakarta, initially constructed with 12 stories, is being redesigned into a 25-story structure to optimize land utilization. This study aims to design the main structural elements of the upgraded building using a Dual System while performing comprehensive structural performance evaluations in accordance with seismic resistance standards. The analysis employed the dynamic response spectrum method via ETABS v22.7, incorporating West Jakarta's specific seismic parameters for soft soil conditions (Site Class SE). Furthermore, the structural model was integrated into Building Information Modeling (BIM) using Autodesk Revit 2025 to generate reinforcement detailing and material quantity estimates. Analytical results demonstrate that the redesigned structural elements successfully satisfy all performance criteria. Story drift remains within safe boundaries, the structure maintains stability against P-Delta effects, and the Strong Column-Weak Beam principle is well fulfilled. The implementation of the Dual System yielded a Special Moment Resisting Frame (SMRF) participation of 79.8% in the X-direction and 53.8% in the Y-direction. Additionally, it restricted the maximum story drift to 50.204 mm well below the 72 mm allowable limit—proving its effectiveness in providing the requisite lateral stiffness and ductility. Overall, the structural design strictly conforms to SNI 1726:2019, SNI 1727:2020, SNI 2847:2019, and SNI 2052:2024 provisions. The BIM integration also successfully produced technical working drawings and highly accurate Quantity Take-Off (QTO) calculations.